Visitors’ Preferences for Tourist Destinations: A Comparative Analysis of Two Contrasting Destination Themes in Lagos, Nigeria - A.O, Olusola; O, Babatola (Journal of Tourism Management Research, 2021)
This research was conducted to investigate motivating factors that influences the preferences of visitors to either Culture-based or the Nature-based destination. The 'Push and Pull' theory of motivation was adopted to identify how Push (motivations) and Pull (destination attraction) influenced visitors’ preferences destinations under investigation, and to identify their relationship. Six (6) sampled destinations- a combination of both Nature-based and Culture-based destinations were randomly selected for this study. Appropriate statistical analyses were carried out and major findings indicated that both Push and Pull factors influences visitors preferences, however Pull factors had more significant effect on visitors preference, especially on the destination visited, indicating that destination attractions has more influence on visitors than their motivations to achieve their desires or needs. The chi-square was used to determine statistical significance among 'Push' and 'Pull' factors and analysis revealed a significant association between preferred Tourist destination and the actual destination visited. Mean measures unveiled that destination attributes/attraction (Pull factors) significantly influenced those that visited nature-based destinations than those that visited culture-based destinations, with attributes: 'Ease of access', ' Overall cleanliness of the destination' and 'Quality of service' with higher rankings. Destination Managers, marketers and all stakeholders in Tourism marketing should pay attention to the intrinsic and extrinsic reasons why people visit in other to grow tourism and because they are fundamental to why people visit or travel. Especially pull factors, as a lot more can be done in this regard, than what pushes visitors due to the unpredictability of human needs.